KONSEP PENDIDIKAN YAYASAN PERGURUAN TAMAN SISWA KOTA PAGARALAM - Yatim Kasianto (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Islamic Education undergone many developments. Cultural  differences among  people make new sciences that  needs solving swatch and  solutions  in  the  development of Islamic  education. Education is the  main  pillar  to  keep  pace  with the development of science  and  technology. We are  not  only  in  demand proficient in  science  and  technology alone  but  also need  to be balanced with spiritual  values in order to avoid gaps in personality. System in education conceptual and  forming an interrelated components between  one  another among  them  are  the  curriculum, principles, objectives,  and  infrastructure that  support so that  the  learning process  so that  the  aut  put  at yield experiencing mental  improvement that  will manifest  in good  acts for himself or in public  life. The research was conducted using qualitative  descriptive  method means  to describe  the actual  state of the  object  on  conscientious and  of course  to get the  materials  and  the  data  the  researchers used,  observation and  interviews  with various  stakeholders am o ng  Community Leaders,  Religious  Leaders,  the  Heir  who accountable, school principals, teachers, Alumni Pagaralam City Government especially those of the head  of the Department of Education, Ministry of Religious Affairs in addition, researchers also refer  to the documents / archive heritage of antiquity  and  then  documented. System and the concept of Unity College Foundation Student Park using the pattern of education system Among the method of educating the spirit of kinship  based on the independence and the nature of nature as instructed founder Ki Hajar Dewantara. In Pagaralam since the establishment of the University Student Park has undergone many ups and  downs quantity  of students from the first period to the present, while the limiting  factor  is caused  partly because  the facilities and  teaching aids as well as educators and the media  learned that only rely on the government so that admintrated school ordered but not yet inventoried continuously. Conditions amid  public  schools also make  the  inevitable  constraints then  the  need  for the  parties  concerned to limit the  admission  of students to the  balance went into  private  school